Lymphocyte activation status in HIV infected intravenous drug users (IVDU) in Kelantan - Musa, Mustaffa; Nor, Norazmi Mohd; Noori, Nazmi Mohd (1999)
Infection with HIV results in profound immunologic changes in the infected host. The host immune system becomes dysregulated and profoundly suppressed culminating in a condition known as AIDS. Although this concept is well accepted, the actual immunopathology of the disease is far from established.Accumulated evidence have shown that the activation or misactivation of the immune system itself may contribute to disease progression (Pantaleo and Fauci, 1994).Thus, higher levels of activated CDS+T cells have been shown to correlate with poorer clinical status and lower CD4+T cell count (Giorgi et al., 1993). Although measurement of the CD4+ T cell level is the current "gold standard" used as a prognostic marker of HIV-disease, it is highly variable among different individuals or even within the same individual.In fact,we have recently demonstrated that the percentage of C04+T cell, a marker suggested to be more stable and less variable than the CD4+T cell absolute count (Taylor et al., 1989) may not necessarily be suitable to be used as a HIV-disease marker for our local stituation (Norazmi and Suam,1994). These data point to the need for separate studies in populations and risk groups other than white homosexual men to identify and clarify prognostic indicators for the development of AIDS.